Proceedings of the 6th Workshop on Eye Gaze in Intelligent Human Machine Interaction: Gaze in Multimodal Interaction 2013
DOI: 10.1145/2535948.2535949
|View full text |Cite
|
Sign up to set email alerts
|

The acoustics of eye contact

Abstract: An important aspect in short dialogues is attention as is manifested by eye-contact between subjects. In this study we provide a first analysis whether such visual attention is evident in the acoustic properties of a speaker's voice. We thereby introduce the multi-modal GRAS 2 corpus, which was recorded for analysing attention in human-to-human interactions of short daily-life interactions with strangers in public places in Graz, Austria. Recordings of four test subjects equipped with eye tracking glasses, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 6 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…• For the Excited trait, speech plays a prominent role with a high correlation to continuous or restricted head movement [66]. On the surprising finding of AUs and speech features impacting eye-contact, prior studies [67] have revealed a low-yet-meaningful correlation between eye contact impressions and vocal acoustic features. Friendliness is best characterized by head movement and voice features, showing that the integration of visual and auditory modalities can be crucial in discerning interviewee friendliness [68].…”
Section: Attention Score-based Interpretationsmentioning
confidence: 99%
“…• For the Excited trait, speech plays a prominent role with a high correlation to continuous or restricted head movement [66]. On the surprising finding of AUs and speech features impacting eye-contact, prior studies [67] have revealed a low-yet-meaningful correlation between eye contact impressions and vocal acoustic features. Friendliness is best characterized by head movement and voice features, showing that the integration of visual and auditory modalities can be crucial in discerning interviewee friendliness [68].…”
Section: Attention Score-based Interpretationsmentioning
confidence: 99%